Tuberculosis: a rare cause of foot and ankle pain - Sahin, Namik; Cansabuncu, Gokhan; Oztas, Savas (The European Research Journal, 2016)
Skeletal tuberculosis is an uncommon infectious disease that occurs in 1-3 % of all tuberculosis cases. Apart from spine it can emerge in weight bearing joints. Tubercular involvement of the ankle is the most uncommon and infrequent amongst those of all joints. If imaging techniques and laboratory results are not sufficient while setting a precise diagnosis, this rare problem should be always taken into consideration just like other infections of the musculoskeletal system. In this paper we present a case of 83-year-old female patient who underwent conservative treatment for ankle tuberculosis.